2015
DOI: 10.1007/s00775-014-1232-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual binding of 14-3-3 protein regulates Arabidopsis nitrate reductase activity

Abstract: 14-3-3 proteins represent a family of ubiquitous eukaryotic proteins involved in numerous signal transduction processes and metabolic pathways. One important 14-3-3 target in higher plants is nitrate reductase (NR), whose activity is regulated by different physiological conditions. Intra-molecular electron transfer in NR is inhibited following 14-3-3 binding to a conserved phospho-serine motif located in hinge 1, a surface exposed loop between the catalytic molybdenum and central heme domain. Here we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…14-3-3 proteins are key regulators of multiple signal transduction cascades relating to diverse physiological and biological processes through hundreds of different protein-protein interactions [ 53 58 ]. The development of bioinformatics, especially the whole genome sequencing, dramatically assisted for the genome wide survey of plant 14-3-3 proteins, for example in Arabidopsis [ 59 , 60 ], rice [ 61 , 62 ], tomato [ 63 ], cotton [ 64 ], and populous [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3 proteins are key regulators of multiple signal transduction cascades relating to diverse physiological and biological processes through hundreds of different protein-protein interactions [ 53 58 ]. The development of bioinformatics, especially the whole genome sequencing, dramatically assisted for the genome wide survey of plant 14-3-3 proteins, for example in Arabidopsis [ 59 , 60 ], rice [ 61 , 62 ], tomato [ 63 ], cotton [ 64 ], and populous [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…interestingly, the phosphorylation of a serine residue in the linker region between the molybdenum and haem domains, 346,347 followed by the binding of a specific regulatory protein, effectively inhibits the enzyme through the inhibition of the intramolecular electron transfer. § § §, [353][354][355][356] another member of the so family is the recently described marC (the fourth mammalian molybdoenzyme, after Xo, ao and so). 357 its physiological function is not known, but it is probably involved in the detoxification of mutagenic and toxic aromatic hydroxyl-amines, such as N-hydroxylated dna base derivates, 358,359 through the catalysis of the reduction of N-and S-hydroxylated compounds at the molybdenum centre (eqn (1.21)), [360][361][362][363] among other possible roles.…”
Section: The Sulfite Oxidase Familymentioning
confidence: 99%
“…352 this phosphorylation creates a recognition site that recruits a specific regulatory protein (one member of the 14-3-3 family), whose binding effectively inhibits the enzyme. [353][354][355][356] (i.e. at the haem of so or the Fad of nar); therefore, intramolecular electron transfer (Mo → haem or Fad → haem → Mo) is, once again, an integral aspect of catalysis.…”
Section: The Sulfite Oxidase Familymentioning
confidence: 99%
“…6, supplementary Tables 1-4), while there was no phosphorylation detectable for recombinant NR purified from E. coli (data not shown). Very recently Chi and co-workers demonstrated that for Arabidopsis NR the interaction with the 14-3-3 protein is mediated by the N-terminus of the enzyme (Chi et al, 2015). We suggest that the Neurospora NR N-terminus may also be involved in enzyme activity regulation by a yet unknown phosphorylation dependent mechanism.…”
Section: Discussionmentioning
confidence: 81%